2015
DOI: 10.1039/c5sm00049a
|View full text |Cite
|
Sign up to set email alerts
|

Soft landing of cell-sized vesicles on solid surfaces for robust vehicle capture/release

Abstract: Based on a concept of a smooth and steady landing of fragile objects without destruction via a soft cushion, we have developed a model for the soft landing of deformable lipid giant unilamellar vesicles (GUVs) on solid surfaces. The foundation for a successful soft landing is a solid substrate with a two-layer coating, including a bottom layer of positively charged lysozymes and an upper lipid membrane layer. We came to a clear conclusion that anionic GUVs when sedimented on a surface, the vesicle rupture occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…As reported previously, the film thickness could be finely controlled by the incubation time, concentration of lysozyme and TCEP, as well as repetitive coating times on the substrate . The resultant PTL nanofilm could stably adhere onto a substrate surface regardless of material type and morphology, which further supported the preparation of surface‐anchored biomimetic vesicles, functional metal and polymer coatings, and effective antimicrobial application via the interplay between functional moieties on the PTL surface and molecules in aqueous solution.…”
Section: Resultssupporting
confidence: 67%
“…As reported previously, the film thickness could be finely controlled by the incubation time, concentration of lysozyme and TCEP, as well as repetitive coating times on the substrate . The resultant PTL nanofilm could stably adhere onto a substrate surface regardless of material type and morphology, which further supported the preparation of surface‐anchored biomimetic vesicles, functional metal and polymer coatings, and effective antimicrobial application via the interplay between functional moieties on the PTL surface and molecules in aqueous solution.…”
Section: Resultssupporting
confidence: 67%
“…It has been reported that an intramolecular disulfide bond is critical to stabilize protein tertiary or quaternary structures. , As a result, a reduction in the number of disulfide bonds led to a mild unfolding of the proteins, which subsequently induced the transformation of chain secondary structures into predominant β-sheets in insulin single crystals . In this regard, Yang et al developed a strategy to realize the nucleation–crystallization of proteins by unfolding native lysozyme, insulin, bovine serum albumin (BSA), or α-lactalbumin via the reduction of their intramolecular disulfide bonds. Tris­(2-carboxyethyl)­phosphine (TCEP) reduced disulfide bonds effectively in lysozyme, , which consequently induced protein unfolding and then self-assembly of unfolded protein chains into short-range β-sheets without complex pre-steps (Figure A). The reduction of disulfide bonds was clearly reflected through Raman spectra and N -(1-pyrenyl)­maleimide (NPM) assay (Figure B), and the transformation to β-sheets was then characterized by circular dichroism (CD) and Fourier transform infrared (FTIR) spectroscopy (Figure C).…”
Section: Nucleation Through Assembly Of Molecular Secondary Structuresmentioning
confidence: 99%
“…The unfolded protein aggregates containing short-range interchain alignments were sensitive to the solvent environment, so the structures of such short-range β-sheet assemblies could be tuned by using different conditions. , Under quasi-equilibrium conditions, short-range β-sheets could be further crystallized to form vast protein nanocrystals (Figure F). These nanocrystals had typical “core–shell” structures, in which crystalline cores, orderly packed from β-sheets, were embedded into amorphous flexible chain shells, similar to the structure of organic–inorganic nanocrystals in biomineralization, and could assemble with a specific orientation into mesocrystals (vide infra).…”
Section: Nucleation Through Assembly Of Molecular Secondary Structuresmentioning
confidence: 99%
“…Through this, a steady capturing and safe landing of GUVs was demonstrated, meanwhile a controlled release was also achieved under mild heat stimuli. 41 These studies portrays the requirement of more researches need to be carried out for exploring the hidden benets biomolecules.…”
mentioning
confidence: 99%